Pseudo-Science and Society in 19th-Century America - Wrobel, Arthur, 1940- (Book collections on Project MUSE., 2015)
"Progressive nineteenth-century Americans believed firmly that human perfection could be achieved with the aid of modern science. To many, the science of that turbulent age appeared to offer bright new answers to life's age-old questions. Such a climate, not surprisingly, fostered the growth of what we now view as "pseudo-sciences"--Disciplines delicately balancing a dubious inductive methodology with moral and spiritual concerns, disseminated with a combination of aggressive entrepreneurship and sheer entertainment. Such "sciences" as mesmerism, spiritualism, homoeopathy, hydropathy, and phrenology were warmly received not only by the uninformed and credulous but also by the respectable and educated. Rationalistic, egalitarian, and utilitarian, they struck familiar and reassuring chords in American ears and gave credence to the message of reformers that health and happiness are accessible to all. As the contributors to this volume show, the diffusion and practice of these pseudo-sciences intertwined with all the major medical, cultural, religious, and philosophical revolutions in nineteenth-century America. Hydropathy and particularly homoeopathy, for example, enjoyed sufficient respectability for a time to challenge orthodox medicine. The claims of mesmerists and spiritualists appeared to offer hope for a new moral social order. Daring flights of pseudo-scientific thought even ventured into such areas as art and human sexuality. And all the pseudo-sciences resonated with the communitarian and women's rights movements."--Publisher's description.